2021
DOI: 10.1016/j.nicl.2021.102736
|View full text |Cite
|
Sign up to set email alerts
|

Brain iron assessment in patients with First-episode schizophrenia using quantitative susceptibility mapping

Abstract: Highlights Patients with first-episode schizophrenia had significantly decreased QSM values in the bilateral substantia nigra, left red nucleus and left thalamus. Patients with first-episode schizophrenia had significantly increased regional volumes in the bilateral putamen and bilateral substantia nigra. QSM provides superior sensitivity over R 2 * mapping in the evaluation of schizophrenia-related iron alterations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 101 publications
1
25
1
Order By: Relevance
“…This novel technique provides enhanced contrast for substantia nigra and VTA by quantifying iron content based on reconstructing magnetic susceptibility sources ( 164 ). A recent study manually segmented the substantia nigra based on quantitative susceptibility maps and reported a volume increase in first-episode schizophrenia patients ( 150 ).…”
Section: Discussion: Current Research Gaps and Potential Developments...mentioning
confidence: 99%
See 1 more Smart Citation
“…This novel technique provides enhanced contrast for substantia nigra and VTA by quantifying iron content based on reconstructing magnetic susceptibility sources ( 164 ). A recent study manually segmented the substantia nigra based on quantitative susceptibility maps and reported a volume increase in first-episode schizophrenia patients ( 150 ).…”
Section: Discussion: Current Research Gaps and Potential Developments...mentioning
confidence: 99%
“…In other psychiatric disorders, VTA/SNc resting-state BOLD FC results are mixed. For instance, regarding substance-related and addictive disorders, reduced connectivity between substantia nigra and caudate nucleus as well as between VTA and medial orbitofrontal cortex, anterior cingulate cortex, and nucleus accumbens has been observed in opioid use disorder ( 150 ), while reduced connectivity of VTA with olfactory tubercle, medial orbitofrontal cortex, and nucleus accumbens was found in patients with internet gaming disorder ( 42 , 151 ). In both major depressive disorder and bipolar disorder, concerning VTA FC, studies observed reduced connectivity with frontal regions ( 149 , 152 ), cerebellum and mediodorsal thalamus ( 152 ) in patients, increased connectivity with pre- and postcentral gyrus, frontal and temporal gyrus, occipital lobe, pons ( 152 ), limbic regions ( 149 , 152 ), cerebellum, and posterior cingulate cortex ( 149 ), or no changes between groups of patients and controls ( 153 ).…”
Section: Distinct Magnetic Resonance Imaging-based Approaches For Stu...mentioning
confidence: 99%
“…146 Hence, iron metabolism is crucial to maintaining integrity in the neurochemical circuits (monoaminergic, GABA, and glutamatergic system). 147 Excess deposition of iron can enhance the formation of free radicals, and it can also lead to OS. On the other hand, depletion in iron supply can result in the depletion of neurodevelopment and long-term neurotransmission changes,.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…QSM yielded the same rank ordering of iron concentration by brain structure, with the lowest in white matter and the highest in the globus pallidus, as well as yielding the expected age-related changes. QSM also proved more sensitive than R2* in assessing changes in brain iron concentration levels in gray matter nuclei for patients with schizophrenia [ 36 ], multiple sclerosis [ 37 , 38 ], and Parkinson’s disease [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%